Antioxidant Activities of Black Soybean Extract (Glycine max (L.) Merr.) and Daidzein as Hydroxyl and Nitric Oxide Scavengers - Irwan, Mulia; Girsang, Ermi; Nasution, Ali Napiah; Lister, I Nyoman Ehrich; Amalia, Annisa; Widowati, Wahyu (Majalah Kedokteran Bandung, 2020)
Free radicals are known as a leading factor in aging. Nitric oxide (NO) and O2•- have been shown to inhibit the synthesis of matrix components and stimulate prolidase activities involved in collagen degradation. Hydroxyl (•OH) radical is a precursor of hyaluronic acid degradation. Antioxidants act as a scavenger for free radicals, creating a possibility to use them to prevent the aging process. Black soybeans (Glycine max (L.) Merr.) contain bioactive compounds that have the ability to scavenge free radicals, including daidzein. Daidzein belongs to the isoflavones group which is the most active compound in black soybean. This study aimed to understand the antioxidant activities of the black soybean extract (BSE) and daidzein compound in the scavenging of •OH and NO radicals and was performed at the Aretha Medika Utama-Biomolecular and Biomedical Research Center (BBRC), Bandung, Indonesia, from September to November 2018. The scavenging activity of •OH was assessed using the deoxyribose method, while the assessment of the scavenging of NO radicals was carried out using the sodium nitroprusside method. BSE and daidzein had an •OH scavenging activity with an IC50 value of 71.07 μg/mL, followed by daidzein with 24.57 μg/mL. A higher NO scavenging activity was seen in BSE with an IC50 of 71.60 μg/mL followed by daidzein with 35.68 μg/mL. Daidzein has a higher antioxidant activity through hydroxyl and nitric oxide scavenging compared to Glycine max (L.) Merr. extract. Hence, daidzein has a higher potential as an anti-aging agent based on the free-radical theory of aging. Aktivitas Antioksidan Ekstrak Kedelai Hitam (Glycine max (L.) Merr.) dan Daidzein sebagai Pemerangkap Hidroksil dan Nitrogen MonoksidaRadikal bebas dikenal sebagai faktor utama penuaan. Nitrogen monoksida (NO) dan O2•- telah terbukti menghambat sintesis komponen matriks dan merangsang aktivitas prolidase yang terlibat dalam degradasi kolagen. Radikal hidroksil (•OH) adalah prekursor dari degradasi asam hialuronat. Antioksidan bertindak sebagai pemerangkap radikal bebas sehingga dapat digunakan untuk mencegah proses penuaan. Kedelai hitam (Glycine max (L.) Merr.) mengandung senyawa bioaktif yang mampu memerangkap radikal bebas, salah satunya adalah daidzein. Daidzein termasuk dalam kelompok isoflavon yang merupakan senyawa paling aktif dalam kedelai hitam. Penelitian ini bertujuan untuk mengetahui aktivitas antioksidan, pemerangkapan •OH dan NO dari ekstrak etanol kedelai hitam (BSE) dan senyawa daidzein. Penelitian ini dilakukan selama bulan September sampai dengan November tahun 2018 di Laboratorium Aretha Medika Utama Biomolecular and Biomedical Research Center (BBRC) Bandung. Pemerangkapan •OH dilakukan dengan metode deoksiribosa, sedangkan pemerangkapan radikal NO dilakukan dengan metode menghitung natrium nitroprusida. BSE dan daidzein memiliki aktivitas pemerangkapan •OH dengan nilai IC50 71,07 μg/mL diikuti oleh daidzein 24,57 μg/mL. Aktivitas pemerangkapan NO pada BSE ditunjukkan dengan IC50 71,60 μg/mL sementara daidzein 35,68 μg/mL. Daidzein memiliki aktivitas antioksidan yang lebih tinggi berdasarkan pemerangkapan •OH dan NO dibanding BSE. Oleh karena itu, daidzein memiliki potensi lebih sebagai antiaging menurut teori penuaan akibat radikal bebas.